Mucinous Prostate Cancer Shows Similar Prognosis to Typical Prostate Acinar Carcinoma: A Large Population-Based and Propensity Score-Matched Study - Zhao, Feng; Yu, Xiaokai; Xu, Mengyou; Ye, Sunyi; Zang, Shoumei; Zhong, Weixiang; Ren, Guoping; Chen, Xin; Yan, Senxiang (Frontiers in Oncology, 2020)
BACKGROUND: Mucinous prostate cancer (PCa) is an extremely rare form of prostate malignancy. To date, the limited knowledge of its biology and outcomes stems from mostly small, single institution experiences. We analyzed the Surveillance, Epidemiology, and End Results (SEER) database to explore the incidence and treatment of mucinous PCa together with its prognostic factors to gain relatively large and consolidated insights. METHODS: Age-adjusted incidence (AAI) rates were evaluated over time. Propensity score matching (PSM) and Kaplan-Meier analyses were used to compare the prognosis between mucinous PCa and typical prostate acinar adenocarcinoma. We assessed cancer-specific survival (CSS) and overall survival (OS) after patient stratification according to summary stage and treatment choice. Cox hazards regression analysis was performed to determine independent predictors of CSS and OS. RESULTS: The AAI in 2016 was 0.24 per million. Patients with mucinous PCa had similar CSS and OS to matched individuals with typical prostate acinar adenocarcinoma. In terms of treatment, 65.3% of mucinous PCa patients underwent surgery, and 23.9% received radiation. Patients who underwent surgery had longer survival (CSS, p=0.012; OS, p<0.001), and patients who received radiation therapy had similar survival to those who did not receive radiation therapy (CSS, p=0.794; OS, p=0.097). A multivariate Cox analysis for CSS and OS showed that older age (CSS: HR: 4.982, p=0.001; OS: HR:4.258, p<0.001) and distant stage (CSS: HR: 40.224, p<0.001; OS: HR: 9.866, p<0.001) were independent prognostic factors for mucinous PCa patients. CONCLUSIONS: Mucinous PCa has an extremely low AAI. Analysis of its outcomes indicates that it is not a more malignant tumor as previously suspected. Mucinous PCa shows a similar prognosis to typical prostate acinar carcinoma. Surgery was associated with prolonged survival. An older age at diagnosis and distant stage was associated with poor survival.